Effect of Meditative Movement Exercises with Breath Control on Depression in Nulliparous Women - Mrunmayi Sandip Gadre1, T Poovishnu Devi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The prevalence of nulliparous women in India is 66% out of 8 million married women. In nulliparous women depression is the most common factor due to various other factors as single mother, or are not able to conceive, low income earners and those in unsupportive social situations. So as to reduce the depressive symptoms or thoughts we can teach them a set of meditative movement exercises specially in women who are nulliparous. Objective: To study the effect of meditative movement exercises with breath control on depression in nulliparous women. Methodology: The study was conducted in and around Karad, Maharashtra, and was carried over a period of 12 weeks. Study was conducted using sample size of 22 nulliparous women with minimal to moderately severe depression. The inclusion criteria was age group of 25 – 35 years females with exclusion criteria as history of high blood pressure, chronic medical illness and major psychiatric problem. Results: Statistical analysis for effect of meditative movement exercise on depression in nulliparous women was extremely significant (P value=0.0001).It was extremely significant during pre-test as well as post- test. So there is improvement in the depression score after teaching the exercises to the individuals. Conclusion: From this study, it can be concluded that the individuals showed improvement in depression levels after teaching them the meditative movement exercises.